Linear Equations Systems of Real and Complex Semi-Quaternions - Alagoz, Yasemin; Ozyurt, Gozde (SPRINGER INTERNATIONAL PUBLISHING AG, 2020)
In this work firstly real semi-quaternion matrices and their properties are examined. Then, 2n x 2n complex adjoint matrix and 4n x 4n real matrix representation of a real semi-quaternion matrix are expressed. Further systems of linear real semiquaternionic equations are investigated and in some of them the 2n x 2n complex adjoint matrix and the 4n x 4n real matrix representation are used. Moreover, matrices which entries are complex semi-quaternions and their 2n x 2n real semi-quaternion matrix representation are presented. Additionally system of linear complex semi-quaternionic equations is described with this 2n x 2n matrix representation. Finally, for a complex semi-quaternion matrix 4n x 4n complex adjoint matrix is introduced. Also, linear complex semi-quaternionic equations systems are examined.
Keywords: Real semi-quaternion; Complex semi-quaternion; Real semi-quaternion matrix; Complex semi-quaternion matrix; Linear real semi-quaternionic equations system; Linear complex semi-quaternionic equations system; MATRICES; AX; Science & Technology - Other Topics